Perception of Influence of Foreign Language Learning on Personality - Medved Krajnović, Marta; Juraga, Ivana (2008)
The argument that language exerts an important influence on the cognitive processes of an individual was first proposed by Edward Sapir, and was also adopted by the sociocultural theory of L. S. Vygotsky and his followers. Lately, the issue of language and identity has become a vibrant topic in SLA research. Based on the responses of 186 proficient learners of English as a foreign language, this paper tries to analyze the link between language learning and the development of personality/ies in the foreign language learning context. The research shows that the issue of language and personality is important to bilinguals, regardless of whether they think that their personality does or does not change when they speak their different languages.
Projekt MZOS
ENG